Produccion y mercadeo de yuca en bolsa (tecnologia de conservacion) - Figueroa, F (International Center for Tropical Agriculture, 1988)
A pilot project was established on Colombia`s Atlantic Coast to promote the agroindustrialization of cassava, based on a simple, low-cost technique developed by CIAT, in which cassava roots are treated directly at the harvest site and preserved in polyethylene bags for up to 3 wk. With this procedure, roots are able to generate the temp. and moisture required for curing, which prevents primary or physiological deterioration; these conditions, however, promote the development of microbial or secondary deterioration, for which the application of a fungicide, thiabendazole, is recommended. Max. time between harvest and packing is 3 h. Background information is given on project justification, objectives, and preliminary studies. Initially implemented in Repelon, the project was extended to other areas. The commercialization of bagged cassava in these areas was analyzed as to cost of raw material, labor, plastic bags, thiabendazole, viaticums, transportation, and administrative expenditures. Financial costs, total costs, and net profitability were also calculated. The plan to extend the supply of bagged cassava is outlined and implies having 15 cooperatives with productive capacity by the 2nd yr of the project. The relationship between production, distribution, and marketing is reviewed. Potential cassava producing regions for supplying bagged cassava for Barranquillan markets are listed. The interinstitutional participation in this project is highlighted. (CIAT)